LEGAL THOUGHTS IN MEASRURING THE STRENGHT OF QIYAS AS FIKIH ZAKAT METHODOLOGY IN INDONESIA - Nispul Khoiri Khoiri (State Islamic University of North Sumatra Indonesia, 2018)
This study aims to know the legal thoughts in measuring the strength of qiyas as the methodology of Jurisprudence of zakat in Indonesia. This research is a qualitative research based on the literature. The results of this study indicate the existence of the fact that the minds that developed visible: First, to support that qiyas is the legal argument including to adopt about the law of prison in Indonesia, this opinion raised by Jumhur ulama especially Imam Syafii who has provided enough space to the existence of qiyas. Secondly, the thought of rejecting qiyas as an argument of Islamic law, this opinion was expressed by the Mu'tazilites, the Zahiriyya and the Imami Shi'ah rejected the use of qiyas absolutely. Thirdly, the group that does not place qiyas as a proposition but qiyas is placed as a method of ijtihad, this opinion put forward by Imam al-Ghazali, Abu Zahrah and Ahmad Hasan. Fourth, the Group of contemporary minds especially developed in Indonesia, such as Hasbi Ash-Shiddieqy and others that qiyas within the boundaries of al-Syafi’i cannot meet the needs because the search process illat so complicated and rigid. Fifth, keterbatasn qiyas in adopting the law of prison in Indonesia lies only to see illat that is naqliyah (nash) means illat which is based on the provisions of texts